THE DEVELOPMENT OF MOBILE BASED GEOGRAPHIC INFORMATION SYSTEM FOR TOURISM IN BALI ISLAND - Surya Mahendra, Gede (Universitas Pendidikan Ganesha, 2013)
This study aims to: (1) develop Mobile Based Geographic InformationSystem for Tourism in Bali Island, (2) Implement the design of Mobile Based Geographic Information System for Tourism in Bali Island. The developed application, is expected to help the various parties in facilitating the provision of information about the tourism destination and the support facilities. This application purposed to provide information to the user in the form of information about the island of Bali, which is able to manipulate various types of data, such as the content of the website, categories of location, location and spot and program JAR, do a search points, do a search spot location, perform location search by district or category and search radius by 10 locations nearby.In the design and implementation of the application, the author used thewaterfall method or which is often called the classic life cycle model is the model in creating the software. The model includes several stages, namely: (1) requirements definition, (2) system and software design, (3) implementation and unit testing, and (4) integration and system testing.The results of this research is an application named